The Effectiveness of Multimodel Learning on Linear Motion Topics to Practice Student’s Problem Solving Skills - Aulia Agustina; Abdul Salam M; Surya Haryandi; Zainuddin Zainuddin; Dewi Dewantara (Berkala Ilmiah Pendidikan Fisika, 2022)
Problem-solving ability is important in learning for the achievement of learning objectives. This research aims to describe the effectiveness of multimodal learning on a linear motion to practice students' problem-solving skills. This research is part of developing digital teaching materials on linear motion in a multimodel setting to practice students' problem-solving skills. Using the ADDIE development model over five stages. The subjects of the class trial were 14 students, 11 girls and 3 boys, in class X MIPA 3 of the school in Banjarmasin. The effectiveness is seen from the achievement in multimodel learning in terms of the result of the pre-test and post-test. The results of the N-gain test show that visualizing 0,40 problems in the category, presenting problems into physics concepts 0,88 in the high category, planning the completion of 0,55 in the medium category, carrying out problem-solving 0,80 in the high category, re-examining and evaluating 0,50 is categorized as high. Overall, the gain was 0,62 in the medium category. The research conclusion shows that multimodel learning is effectively used to practice students' problem-solving skills. The implications in education are creating creative and skilled resources and increasing the quality of education to support the future. Suggestions for further research are to increase the number of test subjects, to guide the process of practising problem skills, to distinguish between pre-test and post-test questions, and to carry out the maximum phases of the learning model.